PENINGKATAN HASIL BELAJAR PESERTA DIDIK PADA MATA PELAJARAN IPAS MENGGUNAKAN MODEL PROBLEM BASED LEARNING (PBL) KELAS IV SD NEGERI 02 SAPAN KOTA SAWAHLUNTO - Fathur Risqi, Afrilio; Yenti, Yesni; Putri Zulkarnaini, Aissy; Waldi, Atri (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This classroom action research investigated the use of Problem Based Learning (PBL) to improve fourth-grade students’ Natural and Social Sciences (IPAS) learning outcomes at SD Negeri 02 Sapan, Sawahlunto. The study was prompted by a low initial mean score of 69.44 and learning mastery of 66.7%, with the minimum criterion set at 75. The research used qualitative and quantitative approaches and involved 18 students in two cycles. Each cycle consisted of planning, action, observation, and reflection. Data were collected through observation sheets for lesson-module design, teacher activities, student activities, and assessment instruments covering attitudes, knowledge, and skills. Qualitative data were analysed descriptively, while quantitative data were analysed using mean scores and mastery percentages. The PBL process employed five phases: problem orientation, learning organization, guided investigation, development and presentation of work, and evaluation of problem solving. The findings showed that teacher and student activities improved from 89.2% in the first meeting of Cycle I to 96.42% in Cycle II. The mean learning outcome increased from 72.7 in Cycle I Meeting 1 to 80.8 in Meeting 2, reaching 89.4 in Cycle II. Knowledge mastery reached 88.9%, with 16 of 18 students attaining the criterion. PBL therefore improved IPAS learning outcomes by engaging students in authentic problems, collaborative investigation, presentation, and reflection.